Consumption of local news in television and newspapers and national pride among Malaysian youth - Tamam, Ezhar (Universiti Putra Malaysia Press, 2011)
Drawing from the development journalism theoretical perspective, consumption of local news is posited to correlate with national pride. However, empirical evidence on the theoretical relationship between local news consumption and national pride among youth in Malaysia is lacking. Hence, a survey was undertaken to determine the relationships of exposure and attention to local news in television and newspapers with national pride and whether the relationships vary by ethnicity. A total of 625 Malay, 416 Chinese, and 112 Indian youths voluntarily participated in the survey. Controlling age, gender and self-identification, the results of multiple regression analysis showed that exposure and attention to local television news significantly predicted national pride, and the relationships were shown to be true for all the three major ethnic samples but these varied in strength. Exposure and attention to local news in the newspapers was a significant predictor of national pride only for the Chinese sample. Implications of the findings were also discussed.